Image is what contracts and dilates (DAPesquisa, 2020)
This essay is a reflective exercise on the de-hierarchization of theatrical functions, the look and the image. The text triggers the report of an accident that occurred with the author himself organized in small theses in a chronological timeline, and from it brings critical discussions about the methodology of the rational look in art history, in the organization of theatrical functions and in the construction and production of images. This essay is about putting two things that cannot be together in the same space-time, contracting and expanding.
Keywords: Theaters; Body image in the performing arts; Performance art